2015
DOI: 10.1128/genomea.01437-14
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Classical Swine Fever Virus Subgenogroup 2.1 from Assam, India

Abstract: We report the complete genome sequence of a classical swine fever virus (genogroup 2.1), isolated from an outbreak in Assam, India. This particular isolate showed a high degree of genetic variation within the subgenogroup 2.1 and may serve as a potential reference strain of the 2.1 genogroup of classical swine fever virus (CSFV) in the Indian subcontinent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The lineage formed by sequences of CSFV strains that circulated in India during 2012–2013 formed a statistically supported cluster (Figure and Table S1). These sequences showed a genetic divergence of 11.9% with the Subgenotype 2.1, where the strains were previously located (Ahuja et al., ), and a genetic divergence compared to the remaining subgenotypes into CSFV Genotype 2 that ranged between 9.1% and 13.8% (Table ). Hence, we propose this lineage to be defined as Subgenotype 2.4 (Figure ).…”
Section: Resultsmentioning
confidence: 75%
“…The lineage formed by sequences of CSFV strains that circulated in India during 2012–2013 formed a statistically supported cluster (Figure and Table S1). These sequences showed a genetic divergence of 11.9% with the Subgenotype 2.1, where the strains were previously located (Ahuja et al., ), and a genetic divergence compared to the remaining subgenotypes into CSFV Genotype 2 that ranged between 9.1% and 13.8% (Table ). Hence, we propose this lineage to be defined as Subgenotype 2.4 (Figure ).…”
Section: Resultsmentioning
confidence: 75%
“…Inner Mongolia) from pigs showing clinical symptoms and pathological lesions resembling mild classical swine fever[48], and characterized as genotype M[49] (PNS BVDV-1.15). Zhu et al[10] reported a noncytopathic strain, genetically closely related to the pig strain ZM-95, associated with a disease cha-AS/GHY/G4 [KM362426][53]. According to E2 region primary sequence analysis, these strains were clustered in the CSFV sub-genogroup 2.1[45] [53].…”
mentioning
confidence: 99%
“…Zhu et al[10] reported a noncytopathic strain, genetically closely related to the pig strain ZM-95, associated with a disease cha-AS/GHY/G4 [KM362426][53]. According to E2 region primary sequence analysis, these strains were clustered in the CSFV sub-genogroup 2.1[45] [53]. The E2 regions of the bovine strains CS/ML/911/IDP/13 [KY860532] and CS/ML/AF/Umiam/14 [KY860531] showed 99% nucleotide identity with…”
mentioning
confidence: 99%
“…-6]. It has been reported that subgenotype 2.1 isolates are distributed in many Asian and European countries and play a dominant role in CSF outbreaks occurring in China, Korea and other countries [3,5,7,8]. With more sequences of 2.1 isolates deposited in the GenBank database, CSFV subgenotype 2.1 has been further divided into 10 sub-subgenotypes (2.1a-2.1j) based on a nucleotide sequence of 190-nt and the 1,119-nt E2 gene [8].…”
mentioning
confidence: 99%
“…The ORF encodes a 3898-amino-acid polyprotein that can be further processed to four structural proteins (Core, E rns , E1, and E2) and eight nonstructural proteins (N pro , P7, NS2, NS3, isolate for GD19/2011 is the sub-subgenotype 2.1a strain Paderborn from Germany [5], and the most distant isolate is the sub-subgenotype 2.1d strain IND/AS/GHY/G4 collected from India [7]. Sequence identity values from the comparison of GD19/2011 and other subgenotype 2.1 isolates at the genome and individual gene levels are shown in Table 1.…”
mentioning
confidence: 99%